2017
DOI: 10.1080/10826084.2017.1322984
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis-Related Problems and Social Anxiety: The Mediational Role of Post-Event Processing

Abstract: Background: Cannabis is the most commonly used illicit drug in the US, and is associated with a range of psychological, social, and physical health-related problems. Individuals who endorse elevated levels of social anxiety are especially at risk for experiencing cannabis-related problems, including cannabis use disorder, despite not using cannabis more often than those with more normative social anxiety. Identification of mechanisms that underlie the relationship between social anxiety and cannabis-related pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Consistent with previous work from the alcohol literature (Bravo et al, 2017;Bravo, Pilatti, et al, 2018), elevated depressive symptoms were associated with higher problem-focused thoughts which, in turn, were associated with greater coping motives that were tied to greater marijuana involvement. These results add to the growing body of research highlighting the mediational role of cognitive variables in the relationship between internalizing symptoms and cannabis disorders in college students (Ecker & Buckner, 2018) and adolescents (Adrian et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…Consistent with previous work from the alcohol literature (Bravo et al, 2017;Bravo, Pilatti, et al, 2018), elevated depressive symptoms were associated with higher problem-focused thoughts which, in turn, were associated with greater coping motives that were tied to greater marijuana involvement. These results add to the growing body of research highlighting the mediational role of cognitive variables in the relationship between internalizing symptoms and cannabis disorders in college students (Ecker & Buckner, 2018) and adolescents (Adrian et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…It is widely understood that the use of addictive substances impacts mental health adversely. Cannabis use has been linked with numerous adverse mental health outcomes including reduced educational achievement [ 1 , 2 ], increased criminal involvement [ 3 ], reduced accomplishment of adult goals (education, employment, stable long term relationships) [ 4 ], depression [ 5 – 7 ] bipolar disorder [ 8 10 ], anxiety [ 7 , 11 13 ], suicidality [ 7 , 10 , 14 , 15 ], schizophrenia, psychosis [ 16 23 ] and other drug use [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the relationship between social anxiety and problematic cannabis use also support this hypothesis. For example, Ecker and Buckner (2017, 2018) suggest that postevent ruminations are an important process for understanding the link between social anxiety and problematic cannabis use, and it has been suggested that a high tendency to be self‐focused is responsible for the emergence of postevent processing (Sluis et al, 2017). Therefore, self‐focused attention is probably an important process in the development and maintenance of problematic cannabis use in socially anxious people.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have also found a positive association between cannabis use or related problems and RNT (du Pont et al, 2018; Ecker & Buckner, 2017, 2018). For example, Ecker and Buckner (2017, 2018) showed that postevent processing, a specific form of RNT about social situations implicated in the development and maintenance of social anxiety (Sluis et al, 2017), was positively associated cross‐sectionally with cannabis‐related problem severity and experimentally with cannabis use frequency. Overall, these data suggest that different forms of RNT could be a risk factor for problematic cannabis use, although the data are limited.…”
Section: Introductionmentioning
confidence: 94%